Effect of Anticoagulants or Antiplatelets Administration on Mortality Case in COVID-19 Patients with Acute Ischemic Stroke: A Systematic Review and Meta-Analysis - Galuh Anis Tasya; Farhan Haidar Fazlur Rahman; Vita Kusuma Rahmawati (AKSONA, 2022)
Acute ischemic stroke (AIS) is a life-threatening complication of COVID-19. This study aims to compare anticoagulant or antiplatelet administration on mortality cases in patients with COVID-19 and AIS. To know the mortality rate in COVID-19 patients with AIS after anticoagulants or antiplatelets therapies. We searched PubMed, ScienceDirect, and Google Scholar for a retrospective cohort study of anticoagulant or antiplatelet effects on mortality cases in COVID-19 and AIS patients. The retrospective cohort was screened using our eligibility criteria, and quality was assessed using the Newcastle Ottawa Scale. Heterogeneity was assessed using the I2 test, and publication bias was evaluated using a funnel plot. All analyses were performed using Review Manager 5.4. Seven retrospective cohort studies involving 58 patients (38 of whom received anticoagulant therapy) met the inclusion criteria. Our combined analysis showed that anticoagulation versus antiplatelet therapy in COVID-19 patients with AIS on the forest plot chart did not significantly affect mortality (OR: 0.9 95% CI 0.42-1.91 I2=0 %). The study showed no significant difference in the incidence of death between anticoagulants or antiplatelet agents to COVID-19 patients with AIS.